Two-component signal transduction system CBO0787/ CBO0786 represses transcription from botulinum neurotoxin promoters in Clostridium botulinum ATCC 3502 - Zhang, Zhen; Korkeala, Hannu; Dahlsten, Elias; Sahala, Elina; Heap, John T.; Minton, Nigel P.; Linström, Miia (2013)
Blocking neurotransmission, botulinum neurotoxin is the most poisonous biological substance known to mankind. Despite its infamy as the scourge of the food industry, the neurotoxin is increasingly used as a pharmaceutical to treat an expanding range of muscle disorders. Whilst neurotoxin expression by the spore-forming bacterium Clostridium botulinum appears tightly regulated, to date only positive regulatory elements, such as the alternative sigma factor BotR, have been implicated in this control. The identification of negative regulators has proven to be elusive. Here, we show that the two-component signal transduction system CBO0787/CBO0786 negatively regulates botulinum neurotoxin expression. Single insertional inactivation of cbo0787 encoding a sensor histidine kinase, or of cbo0786 encoding a response regulator, resulted in significantly elevated neurotoxin gene expression levels and increased neurotoxin production. Recombinant CBO0786 regulator was shown to bind to the conserved -10 site of the core promoters of the ha and ntnh-botA operons, which encode the toxin structural and accessory proteins. Increasing concentration of CBO0786 inhibited BotR-directed transcription from the ha and ntnh-botA promoters, demonstrating direct transcriptional repression of the ha and ntnh-botA operons by CBO0786. Thus, we propose that CBO0786 represses neurotoxin gene expression by blocking BotR-directed transcription from the neurotoxin promoters. This is the first evidence of a negative regulator controlling botulinum neurotoxin production. Understanding the neurotoxin regulatory mechanisms is a major target of the food and pharmaceutical industries alike.